2015
DOI: 10.1534/genetics.115.177345
|View full text |Cite
|
Sign up to set email alerts
|

UNC-16 (JIP3) Acts Through Synapse-Assembly Proteins to Inhibit the Active Transport of Cell Soma Organelles to Caenorhabditis elegans Motor Neuron Axons

Abstract: The conserved protein UNC-16 (JIP3) inhibits the active transport of some cell soma organelles, such as lysosomes, early endosomes, and Golgi, to the synaptic region of axons. However, little is known about UNC-16's organelle transport regulatory function, which is distinct from its Kinesin-1 adaptor function. We used an unc-16 suppressor screen in Caenorhabditis elegans to discover that UNC-16 acts through CDK-5 (Cdk5) and two conserved synapse assembly proteins: SAD-1 (SAD-A Kinase), and SYD-2 (Liprin-a). Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(92 citation statements)
references
References 68 publications
(124 reference statements)
4
88
0
Order By: Relevance
“…In the accompanying study (Edwards et al 2015), our analysis of cell soma organelle trafficking in the same motor neurons supports a general organelle transport function for SAD-1, SYD-1, SYD-2, and CDK-5, as well as STRD-1 (STRADa), a protein shown to directly interact with SAD-1 (Kim et al 2010). The demonstration that sad-1 and syd-2 null mutants have wild-type rates of coordinated locomotion (Edwards et al 2015) also suggests that the axons and dendrites in the cholinergic motor neurons that mediate this locomotion maintain their proper identity despite the transport defect. Despite the lack of evidence for an axon-identity defect in the synapse-assembly mutants in C. elegans cholinergic motor neurons, prior studies have demonstrated a clear role for SAD-1's mammalian orthologs SAD-A and SAD-B in specifying axon identity in forebrain neurons (Kishi et al 2005), where SAD-A/B act in a pathway downstream of the LKB1 kinase (Barnes et al 2007).…”
Section: Dual Roles For Synapse-assembly Proteins 113supporting
confidence: 67%
See 4 more Smart Citations
“…In the accompanying study (Edwards et al 2015), our analysis of cell soma organelle trafficking in the same motor neurons supports a general organelle transport function for SAD-1, SYD-1, SYD-2, and CDK-5, as well as STRD-1 (STRADa), a protein shown to directly interact with SAD-1 (Kim et al 2010). The demonstration that sad-1 and syd-2 null mutants have wild-type rates of coordinated locomotion (Edwards et al 2015) also suggests that the axons and dendrites in the cholinergic motor neurons that mediate this locomotion maintain their proper identity despite the transport defect. Despite the lack of evidence for an axon-identity defect in the synapse-assembly mutants in C. elegans cholinergic motor neurons, prior studies have demonstrated a clear role for SAD-1's mammalian orthologs SAD-A and SAD-B in specifying axon identity in forebrain neurons (Kishi et al 2005), where SAD-A/B act in a pathway downstream of the LKB1 kinase (Barnes et al 2007).…”
Section: Dual Roles For Synapse-assembly Proteins 113supporting
confidence: 67%
“…Previous studies have found that CDK-5 and the synapse-assembly protein SYD-2 inhibit the dynein-mediated dendritic accumulation of DCVs (Goodwin et al 2012;Goodwin and Juo 2013). CDK-5 and SYD-2 also act together in the same system to inhibit the dendritic accumulation of lysosomes in mutants lacking UNC-16 (Edwards et al 2015). To determine if CDK-5 and/or SYD-2 inhibit DCVs from accumulating in dendrites in unc-104(ce782) mutants, we quantified dendritic and cell soma DCV densities in cdk-5 and syd-2 single mutants and the corresponding doubles with unc-104(ce782).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations